A carboxylic acid functionalized benzimidazole-based supramolecular gel with multi-stimuli responsive properties. (6th April 2016) - Yao, Hong; Wu, Hong-Ping; Chang, Jing; Lin, Qi; Wei, Tai-Bao; Zhang, You-Ming
Abstract : We fabricated an organogel C11-OG and a novel metallogel Pb-MG, both of which exhibit strong blue AIEE in gel states. Abstract : A novel supramolecular gelator (C11) based on a carboxylic acid-functionalized benzimidazole was synthesized, which could form an organogel (C11-OG) and generate a metallogel (Pb-MG) with Pb 2+ . Both of the supramolecular gels exhibit aggregation-induced enhanced emission (AIEE). The Pb-MG shows outstanding reversible sol–gel transitions induced by the change in temperature, EDTA and Na2 S. It has the potential to be widely applied in materials science.